Translation, cross-cultural adaptation and validity of the Brazilian version of the Foot and Ankle Ability Measure questionnaire. Issue 25 (3rd December 2016) - Moreira, Tarcísio Santos; Magalhães, Lívia de Castro; Silva, Rafael Duarte; Martin, RobRoy L.; Resende, Marcos A. de
Abstract: Purpose: To translate and cross-culturally adapt the Foot and Ankle Ability Measure (FAAM) questionnaire and verify the psychometric properties of the Brazilian–Portuguese version of this instrument. Methods: Analysis of validity was carried out by applying the Rasch model and evaluating correlations with the Short Form-36 (SF-36) Physical Function (PF) subscale. Test–retest reliability and internal consistency were analyzed with the intraclass correlation coefficient (ICC2, 1 ) and Cronbach's alpha tests, respectively. Results: Ninety subjects with various foot and ankle musculoskeletal disorders (age 37.05 SD 10.49 years) were included. The ICC2, 1 was 0.88 and 0.82 with Cronbach's alphas of 0.93 and 0.90 for the "Activities of Daily Living" (ADL) and "Sports" subscales, respectively. Correlations with the SF-36 PF were 0.78 ( p  < 0.01, CI95 : 0.62–0.87) and 0.65 ( p  < 0.01, CI95 : 0.45–0.79) for the ADL and Sports subscales, respectively. Item reliability indices in Rasch analysis were 0.91 (ADL) and 0.84 (Sports). Three items from the ADL subscale (14.2%) did not match the expectations of the model. All items from the Sports subscale fit the model. Conclusions: There is evidence of validity and reliability of the FAAM-Brazil. Rasch analysis indicated that three items of the ADL subscale did not fit the model in the sample studied. Implications for Rehabilitation: Self-report questionnaires are commonly used in both clinical practice and research because of their ability to efficiently collect information. If the instrument is created properly, the information collected can be used to interpret the effect of clinical conditions on physical function. The Foot and Ankle Ability Measure (FAAM) is an evaluative instrument that assesses functional limitations for those with foot- and ankle-related disorders. It was translated into four languages and has evidence of validity, reliability, and responsiveness. Evidence of validity and reliability is provided for the FAAM-Brazil when applied to subjects with a wide range of foot and ankle musculoskeletal disorders.